Analysis of simple sequence repeat (SSR) structure and sequence within Epichloë endophyte genomes reveals impacts on gene structure and insights into ancestral hybridisation events - Clayton W; Eaton CJ; Dupont PY; Gillanders T; Cameron N; Saikia S; Scott DB (Public Library of Science (PLoS))
Epichloë grass endophytes comprise a group of filamentous fungi of both sexual and asexual species. Known for the beneficial characteristics they endow upon their grass hosts, the identification of these endophyte species has been of great interest agronomically and scientifically. The use of simple sequence repeat loci and the variation in repeat elements has been used to rapidly identify endophyte species and strains, however, little is known of how the structure of repeat elements changes between species and strains, and where these repeat elements are located in the fungal genome. We report on an in-depth analysis of the structure and genomic location of the simple sequence repeat locus B10, commonly used for Epichloë endophyte species identification. The B10 repeat was found to be located within an exon of a putative bZIP transcription factor, suggesting possible impacts on polypeptide sequence and thus protein function. Analysis of this repeat in the asexual endophyte hybrid Epichloë uncinata revealed that the structure of B10 alleles reflects the ancestral species that hybridized to give rise to this species. Understanding the structure and sequence of these simple sequence repeats provides a useful set of tools for readily distinguishing strains and for gaining insights into the ancestral species that have undergone hybridization events.